Smart Monitoring Suhu Akuarium Arwana Berbasis IoT (ESP32) - Syaifullah, Moh. (J-Eltrik, 2024)
The arowana is a freshwater ornamental fish with high market value, requiring proper and meticulous care. One crucial factor in its maintenance is maintaining the water temperature within an optimal range of 26°C to 30°C. Deviations from this temperature range can cause stress in arowana fish, adversely affecting their health and growth. Therefore, a system for automatic and real-time temperature monitoring and control based on Internet of Things (IoT) technology is necessary. This research developed a Smart Monitoring System for Arowana Aquarium Temperature based on IoT, utilizing an ESP32 microcontroller and a DS18B20 temperature sensor, integrated with the Blynk application on Android devices. The system operates with automatic logic: when the water temperature drops below 26°C, the heater turns on; when it exceeds 30°C, the cooling fan is activated. If the temperature is within the 26–30°C range, both devices remain off. All temperature data is displayed in real-time on the Blynk application. The implementation results demonstrate that the system effectively maintains stable water temperatures within the desired range, reduces stress on the arowana, enhances maintenance efficiency, and provides convenience for the fish owner by enabling remote monitoring of the aquarium's conditions. Key words: Arowana fish, water temperature, Internet of Things, Blynk